Play in the Early Years - Fleer, Marilyn (Port Melbourne, A : Cambridge University Press, 2013)
Play-based learning is an important focus in the Early Years Learning Framework and in early childhood education degrees. This book examines play across time, culture and institutions, and analyses key theories from classical and contemporary perspectives. Fleer from Monash.
Keywords: Play